2017
DOI: 10.1080/10245332.2017.1403736
|View full text |Cite
|
Sign up to set email alerts
|

βSglobin gene haplotype and the stroke risk among Egyptian children with sickle cell disease

Abstract: This study provides a relevant contribution to our understanding of the anthropological and historical background of the population in Egypt where Benin haplotype is the commonest β globin gene haplotype and homozygous Benin/Benin is associated with higher stroke risk than other haplotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The second prevalent detected haplotype was Benin haplotype, with a frequency of 26.9%. This haplotype is the most predominant in many parts of the world, particularly African continent and Middle East countries [13,17]. The frequency of the Benin haplotype in the current study is consistent with earlier reports from Sudan and Brazil [27,30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The second prevalent detected haplotype was Benin haplotype, with a frequency of 26.9%. This haplotype is the most predominant in many parts of the world, particularly African continent and Middle East countries [13,17]. The frequency of the Benin haplotype in the current study is consistent with earlier reports from Sudan and Brazil [27,30].…”
Section: Discussionsupporting
confidence: 92%
“…The isolated DNA was stored at -20 °C until use in subsequent analyses. β-globin haplotyping assay was carried out for six specific loci of the β globin gene cluster by using polymerase chain reaction (PCR) followed by restriction fragment length polymorphisms (RFLP) as described previously [17]. The six loci were amplified using specific sets of primers to generate PCR fragments of 760 bp, 650 bp, 323 bp, 635 bp, 914 bp and 328 bp (Supplementary Table 1).…”
Section: Hemoglobinmentioning
confidence: 99%
“…Several authors have highlighted the interest of studying hemoglobin haplotypes for individuals with hemoglobin disorders as a modulation of the clinical pro le of the disease can occur (7)(8)(9)(10)(11)(12)(13)(14). In Côte d'Ivoire, not data was available on these haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These haplotypes have different geographic origins (5,6). The presence of some haplotypes can reduce the SCD symptoms, whereas other ones amplify clinical manifestations (7)(8)(9)(10)(11)(12)(13)(14). To determine these haplotypes, speci c restriction enzymes (RE) are used after PCR ampli cation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that patients with AI or SEN haplotypes have the highest HbF levels associated with fewer clinical manifestations, and this is likely due to a higher prevalence of the Xmn1-HBG2 polymorphism [ 6 , 14 ]. BEN and CAM haplotypes exhibit an intermediate disease severity [ 20 ]. Meanwhile, patients with CAR haplotypes have the lowest HbF levels, and therefore the worst clinical course [ 21 ].…”
Section: Introductionmentioning
confidence: 99%